IoT-based Recording of Waste Types and Weights in Waste Processing System - Ishlakhuddin, Fauzan; Muhamad, Fachrul Pralienka Bani; Ismantohadi, Eka; Jannah, Miftahul (Diponegoro University, 2025)
Effective waste management requires the separation of waste types into categories such as organic, non-organic, and recyclable. This is necessary because not all types of waste can be processed. Therefore, accurate recording of waste types and weights is crucial in waste processing. A common issue today is that waste data is still recorded manually, leading to a lack of accuracy in the records. This research aims to develop an IoT-based waste type recording tool that can accurately record the weight and type of waste by retrieving values from a scale and transmitting the data in real-time to a waste processing system. The device development method used is the prototype model. This research successfully connected to and retrieved values directly from the Sayaki T-18 digital scale, ensuring that the weight values sent to the system are more accurate. During the testing of the developed IoT device, it accurately recorded and transmitted the quantity and type of waste as specified by the user, and the data stored in the system matched the test data accurately.